Optically transparent melamine-formaldehyde polymers modified with proton acceptors - Lebedev, V.V.; Blank, T.A.; Avramenko, V.L.; Eksperiandova, L.P.; Mishurov, D.A.; Titskaya, V.D.; Shadrikov, A.S. (Functional Materials, 2009)
Investigation of reaction water binding in melamine-formaldehyde polymers with proton accepting compounds has shown that the use of dimethyl sulfoxide in 1/1 (v/v) ratio provides preparation of optically transparent materials. Introduction of dimethyl formamide and dimethyl sulfoxide improves the main characteristics of the material, but modification with dimethyl formamide reduces the polymer transparency. Дослідження процесів зв'язування реакційної води у меламіно-формальдегідних полімерах за допомогою протоноакцепторних сполук показало, що при застосуванні диметилсульфоксиду в об'ємному співвідношенні 1:1 можна одержати оптично прозорі матеріали. Введення диметилформаміду та диметилсульфоксиду покращує основні характеристики матеріалу, однак модифікація диметилформамідом знижує прозорість полімерів. Исследование процессов связывания реакционной воды в меламино-формальдегидных полимерах с помощью протонно-акцепторных соединений показало, что при использовании диметилсульфоксида в объемном соотношении 1:1 можно получить оптически прозрачные материалы. Введение диметилформамида и диметилсульфоксида улучшает основные характеристики материала, однако модификация диметилформамидом снижает прозрачность полимеров.